2008
DOI: 10.1111/j.1530-0277.2008.00639.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Developmental Exposure to Ethanol on Caenorhabditis elegans

Abstract: Background: We investigated the effects of chronic ethanol exposure on physical development, reproduction, and life expectancy of Caenorhabditis elegans, a microscopic nematode worm. It has a small nervous system of 302 neurons and a short lifespan of 2 to 3 weeks.Methods: In this study, the worms were chronically exposed to varying concentrations of ethanol for different periods of their life: for their entire lifespan, during larval development only, and during adulthood only. In addition, the worms were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 47 publications
2
50
0
Order By: Relevance
“…The severity of the defects is dose dependent (Davis, Li, & Rankin, 2008), and the pathway of ethanol catabolism appears to be conserved between nematodes, flies, and mammals (Alaimo et al, 2012).…”
Section: Studies On Ethanol Toxicitymentioning
confidence: 99%
“…The severity of the defects is dose dependent (Davis, Li, & Rankin, 2008), and the pathway of ethanol catabolism appears to be conserved between nematodes, flies, and mammals (Alaimo et al, 2012).…”
Section: Studies On Ethanol Toxicitymentioning
confidence: 99%
“…While this work is largely outside the scope of this review, it is noteworthy that studies utilizing C. elegans (Davis et al 2008), and chicken models (Pennington et al 1983; Cartwright and Smith 1995) have revealed important adverse effects of alcohol on craniofacial development, growth, the developmental trajectory, reproductive maturity, and overall longevity, and have elucidated how the dose and timing of alcohol exposure may contribute to outcomes. In support of the significance of these findings in non-mammalian models is work on the effects of alcohol on mammalian embryos.…”
Section: Risk Factors For Alcohol Teratogenicity and Fasdmentioning
confidence: 99%
“…For FASD research, the microscopic nematode worm C. elegans is the most commonly used. While mammals offer significant advantages over invertebrates when examining brain structures or complex behaviors, simple invertebrates such as C. elegans can be extremely useful when examining basic biological development at the cellular, molecular, and genetic levels (145). The complete genome of C. elegans has been sequenced, and the simple nervous system contains only 302 neurons with 5000 synapses.…”
Section: Factors To Consider When Modeling Fasdmentioning
confidence: 99%
“…A significant disadvantage to using this model is that the egg develops outside of the body and therefore alcohol exposure cannot occur as it does in human beings (via the placental membrane following oral ingestion). Instead, C. elegans eggs or newly hatched larvae are exposed to ethanol through bath application (145). Another disadvantage with this model is that BACs cannot be directly measured.…”
Section: Factors To Consider When Modeling Fasdmentioning
confidence: 99%